INFLUENCE OF STOCKS OF NITROGEN AND PHOSPHORUS ON DISTRIBUTION OF WATER HYACINTH (Eichhornia crassipes) IN LAKE NOKOUE IN BENIN. - Saizonou, Mickael; SOCLO, HOUÉNOUKPO HENRI (My University, 2015)
The present study aimed to evaluate the influence of nitrogen and phosphorus stocks on the distribution of water hyacinth in Lake Nokoue. Apart from conventional water quality parameters, the range of concentrations (in mg /L) of the parameters indicative of nitrogenous pollution and phosphorus and dissolved oxygen measured in the lake is as follow: NO2- (0.01 to 74); NO3- (1.00 to 24.94); NH4+ (0.02 to 8.80); PO43- (0.04 to 7.65); Ptotal (0.0 to 1.2); O2dissolved (2.10 to 4.25). The concentrations of nutrients are in most of the cases above the WHO and Benin standards related to surface water quality. Such high concentrations justify the invasion of the lake by the water hyacinth (Eichhornia Crassipes) when salinity levels are low (< 3 ‰) in these water.
Keywords: Pollution; lake Nokoue; water hyacinth.